Understanding Patient Satisfaction Using SERVQUAL-Kano: The Moderating Role of Patient Trust and the Mediating Role of Waiting Time Tolerance - Rafelito Kharisma Rahardjo; Desak Made Febri Purnama Sari; Gede Sri Darma; Putu Dyah Permatha Korry (Master of Management, School of Business and Management, Petra Christian University, 2025)
This study examines factors influencing patient satisfaction at private primary healthcare facilities (FKTP) in Bali, focusing on SERVQUAL dimensions, waiting time tolerance, patient trust, and Kano model attributes. Using a quantitative design and Partial Least Squares Structural Equation Modelling (PLS-SEM) on data from 188 respondents, the study found that assurance and patient safety significantly influence patient satisfaction, while tangibility, reliability, empathy, and responsiveness did not show significant effects. Assurance and responsiveness positively influence waiting time tolerance, which itself positively influences satisfaction. Waiting time tolerance did not mediate the relationship between SERVQUAL dimensions and satisfaction. Patient trust did not directly influence patient satisfaction but negatively moderated the impact of tangibility on satisfaction. Kano model attributes – categorized as attractive, one-dimensional, and must-be – showed no significant direct effect on satisfaction, reflecting their asymmetric and non-linear nature. The findings suggest that private FKTP should prioritize maintaining high assurance and patient safety standards alongside attractive features such as 24-hour service and patient feedback systems. Integrating patient safety into the SERVQUAL framework is recommended in the healthcare sector. Future research should explore patient satisfaction through longitudinal and qualitative approaches to better capture the dynamic nature of healthcare service quality.